PERAN KARANG TARUNA DALAM PEMBERDAYAAN MASYARAKAT MELALUI PENDAMPINGAN UMKM (STUDI KASUS KARANG TARUNA MAHAKARYA DESA SUKAMAJU SUKABUMI - Bagya Husna Fatwa; Rasid Rasid (Jurnal Kommunity Online, 2022)
Karang Taruna is a forum for developing the young generation of nonpartisan, which grows on the basis of awareness and a sense of social responsibility from, by and for the community, especially the younger generation in the village kelurahan or the social community equivalent, which is mainly engaged in social welfare.The research method used is qualitative with descriptive types. Data collection techniques in this study are observation, interviews and documentation. This study used the role theory of Jim Ife (1995) which explained that the group's role can be known through the facilitative role, the role of education, the role of representation, and technical roles.The results of the research obtained show that in MSME assistance by Karang Taruna Mahakarya has begun well with the facilitation role through the supply of equipment for the production and supply of product labels, the role of representation in the form of an understanding of market competition and the coral cadets also provide a solution, Technical roles through mentoring in terms of marketing and promotion.